Comments on Survey of Attitudes on Management Auditing: A Reply. - Smith, Charles H.; Lanier, Roy A.; Taylor, Martin E. (The Accounting Review, 1973)
Abstract Presents a reply to a comments made on the article "The Need for and Scope of the Audit of Management: A Survey of Attitudes," which was published in the April 1972 issue of the journal "The Accounting Review." Lack of understanding on the objective of the survey; Difficulty in implementing an audit of management; Involvement of a subjective judgment in any internal control evaluation.